Effect of substrate bias on friction coefficient, adhesion strength and hardness of tin-coated tool steel - Hamzah, Esah; Ali, Mubarak; Mohd. Toff, Mohd. Radzi (World Scientific Publishing, 2006)
In the present study, TiN coatings have been deposited on D2 tool steel substrates by using cathodic arc physical vapor deposition technique. The objective of this research work is to determine the usefulness of TiN coatings in order to improve the micro-Vickers hardness and friction coefficient of TiN coating deposited on D2 tool steel, which is widely used in tooling applications. A Pin-on-Disc test was carried out to study the coefficient of friction versus sliding distance of TiN coating deposited at various substrate biases. The standard deviation parameter during tribo-test result showed that the coating deposited at substrate bias of -75 V was the most stable coating. A significant increase in micro-Vickers hardness was recorded, when substrate bias was reduced from -150 V to zero. Scratch tester was used to compare the critical loads for coatings deposited at different bias voltages and the adhesion achievable was demonstrated with relevance to the various modes, scratch macroscopic analysis, critical load, acoustic emission and penetration depth. A considerable improvement in TiN coatings was observed as a function of various substrate bias voltages.